Modelo de simulación para el sistema de distribución de la empresa Envía Colvanes S.A.S para la zona cuatro en la ciudad de Bogotá. (2023)
Simulation is the process of designing and developing a computer model of a system or process and conducting experiments on this model for the purpose of understanding its behavior or evaluating various strategies with which it can be operated. (Marquez days, Sanmartín Mendoza, & Céspedes, 2013). Based on the above, it is intended to simulate a vehicle routing system for the distribution of merchandise in Bogotá for the company Envía Colvanes S.A.S in zone four that allows optimizing the operation.